10‐1: Color Speckle Evaluation Using Monochromatic Speckle Measurements. Issue 1 (May 2016) - Kinoshita, Junichi; Aizawa, Hitoshi; Takamori, Akira; Yamamoto, Kazuhisa; Murata, Hiroshi; Kuroda, Kazuo
Abstract : Color speckle distributions around a white point in CIE chromaticity diagram are evaluated using the measured spatial distributions of monochromatic speckle of the projected three primary‐color uniform images. The evaluated color speckle distributions well agree with the distributions calculated by Monte Carlo simulation.